Documents on the papal plenary indulgences 1300-1517 preached in the Regnum Teutonicum - Jenks, Stuart (Later Medieval Europe Ser., 2018)
Intro -- ‎Contents -- ‎Acknowledgements -- ‎List of Tables, Maps, Graphs and Illustrations -- ‎Tables -- ‎Maps -- ‎Graphs -- ‎Illustrations -- ‎Introduction -- ‎Notes on the Diplomatic Form of the Edition -- ‎A Brief Guide for the Uninitiated -- ‎The Basics -- ‎Peraudi, Summaria declaratio -- ‎Jubilee Indulgences -- ‎Crusading Indulgences -- ‎Penitentiary -- ‎Development to 1517 -- ‎Chapter 1. Jubilee Indulgence 1300 -- ‎Chapter 2. Jubilee Indulgence 1350 -- ‎Chapter 3. Jubilee Indulgence 1389 -- ‎Chapter 4. Crusade Indulgence against the Hussites 1420 -- ‎Chapter 5. Plenary Indulgence of the Council of Basel for Financing the Negotiations with the Greeks on the Union of Both Churches 1436/38 -- ‎Chapter 6. Jubilee Indulgence 1450 -- ‎Chapter 7. Crusade against the Turks 1455 -- ‎Chapter 8. Crusade against the Turks 1463 -- ‎Chapter 9. Crusade Indulgence against King George Podiebrad of Bohemia 1465/71 -- ‎Chapter 10. Jubilee Indulgence 1475 -- ‎Chapter 11. Indulgence for the Church of Saintes 1476/88 -- ‎Chapter 12. Plenary Indulgence for the Order of St Mary Magdalene in Strasbourg 1479 -- ‎Chapter 13. Indulgence for the Order of St John of Jerusalem in Defense of Rhodes 1479/82 -- ‎Chapter 14. Indulgence in Aid of the War against the Turks 1489 -- ‎Chapter 15. Jubilee Indulgence 1500 -- ‎Chapter 16. Indulgence in Aid of the War against the Turks 1501/03 -- ‎Chapter 17. Indulgence in Aid of the War against the Russians and Tartars in Livonia 1503/06 -- ‎Chapter 18. St Peter Indulgence 1506 -- ‎Chapter 19. Indulgence in Aid of the War against the Russians and Tartars in Livonia 1507/10 -- ‎Chapter 20. Indulgence in Aid of the Reconstruction of the Towers of the Constance Minster 1513/14 -- ‎Chapter 21. Indulgence for the Hospital of the Holy Spirit in Rome 1514/18 -- ‎Chapter 22. Indulgence in Aid of the Dominicans of Augsburg 1514/17.